2015
DOI: 10.3390/s150921294
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge-Based Query Construction Using the CDSS Knowledge Base for Efficient Evidence Retrieval

Abstract: Finding appropriate evidence to support clinical practices is always challenging, and the construction of a query to retrieve such evidence is a fundamental step. Typically, evidence is found using manual or semi-automatic methods, which are time-consuming and sometimes make it difficult to construct knowledge-based complex queries. To overcome the difficulty in constructing knowledge-based complex queries, we utilized the knowledge base (KB) of the clinical decision support system (CDSS), which has the potent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 24 publications
(27 reference statements)
0
9
0
Order By: Relevance
“…Previously, we developed automated methods for knowledge-based query construction, assisting the medical practitioners in query preparation. 24,25 This work is a step forward to focus on evidence quality evaluation and CAG.…”
Section: Objectivementioning
confidence: 99%
“…Previously, we developed automated methods for knowledge-based query construction, assisting the medical practitioners in query preparation. 24,25 This work is a step forward to focus on evidence quality evaluation and CAG.…”
Section: Objectivementioning
confidence: 99%
“…While our study may not yet translate into improved patient outcomes, certainly others have shown that the use of CDSS can improve efficiency. Afzal et al [ 22 ] describes the use of CDSS to gather information in a more efficient manner. It is reasonable to hypothesize that improving efficiency may be a key component in improving patient outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Prescribing CDSS is appropriate for the enhancement of outcomes when facing systematic challenges relating to clinical knowledge concerning the health records of patients (Kuperman et al, 2007). This method enriches the clinical knowledge of secondary care health providers through two steps (basic and advanced) (Afzal et al, 2015). In detail, the basic step is as follows; practitioners will be able to check the allergy as a side-effect of a drug, guidance regarding the dosage, interactions between various given drugs, and scrupulously examine the issue of duplicate therapy (Ungar et al, 2008).…”
Section: Patient Safetymentioning
confidence: 99%